Prevalence of, associations with, and prognostic role of anemia in heart failure across the ejection fraction spectrum. (1st January 2020) - Savarese, Gianluigi; Jonsson, Åsa; Hallberg, Ann-Charlotte; Dahlström, Ulf; Edner, Magnus; Lund, Lars H.
Abstract: Background: The role of anemia in heart failure with mid-range and preserved ejection fraction (HFmrEF, EF 40–49% and HFpEF, EF ≥50%) is unknown. We aimed to compare prevalence of, associations with, and prognostic role of anemia in HF across the EF spectrum. Methods: In patients from the Swedish HF Registry, we assessed the associations between clinical characteristics and anemia (hemoglobin <120 g/L in women and <130 g/L in men) by multivariable logistic regression, and between anemia, composite of all-cause death and HF hospitalization and all-cause death alone by multivariable Cox regression. Results: Of 49, 985 patients with HF (anemia = 34%), 23% had HFpEF (anemia = 41%), 21% had HFmrEF (anemia = 35%) and 55% had HFpEF (anemia = 32%). Higher EF was independently associated with higher likelihood of concomitant anemia. Important predictors of anemia across the EF spectrum were male sex, older age, worse New York Heart Association class and renal function, lower systolic blood pressure, higher N-Terminal B-type natriuretic peptides levels, diabetes, valvular disease and in-patient status. Anemia had adjusted hazard ratios (95% CI) for mortality or HF hospitalization 1.24 (1.18–1.30) in HFpEF, 1.26 (1.19–1.34) in HFmrEF and 1.14 (1.10–1.19) in HFrEF; p interaction EF = 0.003; and for mortality 1.28 (1.20–1.36) in HFpEF, 1.21 (1.13–1.29) in HFmrEF, and 1.30 (1.24–1.35) in HFrEF; p interaction EF = 0.22. Conclusions: In this nation-wide registry, prevalence of anemia was higher in HFpEF vs. HFmrEF vs. HFrEF, but was associated with a similarly increased risk of death across the EF spectrum, with greater risk of death or HF hospitalization in HFpEF and HFmrEF vs. HFrEF. Highlights: Prevalence of anemia is higher in HFpEF vs. HFmrEF vs. HFrEF Relevant independent predictors of anemia are higher ejection fraction, older age, male sex, in-patient vs. out-patient status, and more severe HF measured by higher NYHA class and NT-proBNP and lower systolic blood pressure and eGFR Anemia is independently associated with the composite of all-cause mortality or HF hospitalization, and with all-cause mortality alone Anemia is independently associated with similar risk of death regardless of EF, but with greater risk of HF hospitalization in HFpEF and HFmrEF as compared to in HFrEF